Legal Review of the Implementation of People's Business Credit Regulations on Maximum Credit Ceiling Limits - Tjahyawinata, Jenny Theresia; Sihabudin, Sihabudin; Dewantara, Reka (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
This study analyzes the implementation of Coordinating Minister for Economic Affairs Regulation No. 1 of 2023 concerning People's Business Credit (KUR), with a specific focus on the maximum credit ceiling policy and its effect on MSMEs’ access to financing. The research is framed within an empirical legal approach using a case study of a selected banking unit to examine the alignment between regulatory provisions and lending practices. Findings reveal a significant gap: although the regulation allows for unsecured loans up to Rp100 million, many banks still impose collateral requirements. This practice undermines the principle of equitable access to credit, particularly affecting strategic sectors such as agriculture and micro-trade. Administrative constraints, limited legal literacy among borrowers, and weak regulatory oversight were identified as major implementation barriers. The study contributes to economic legal theory by highlighting the intersection of access equity and regulatory practice, and offers practical recommendations for policy harmonization between regulatory frameworks and banking practices. The urgency to reformulate a more flexible credit ceiling and to enhance institutional capacity for inclusive KUR distribution is underscored.